2006
DOI: 10.1128/aem.00773-06
|View full text |Cite
|
Sign up to set email alerts
|

Biotyping of Enterotoxigenic Staphylococcus aureus by Enterotoxin Gene Cluster ( egc ) Polymorphism and spa Typing Analyses

Abstract: Thirty-five Staphylococcus aureus strains, including 10 reference strains and 25 strains recovered from clinical specimens and food samples, were analyzed by PCR REA (restriction endonucleases analysis) of the egc operon and spa typing. Nineteen spa types and seven different egc operons, including four putative new egc variants, were revealed. In 13 strains, allelic variants of sei and/or seg were found. By an analysis of their nucleotide sequence identities, a new homogeneous cluster of a sei variant, called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…Although sei and seg are encoded on the same pathogenicity island, the enterotoxin gene cluster egc, frequently only sei or seg was detected using the primer pairs described previously (26,28). This effect may be caused by the polymorphisms that were found in egc and that impede the annealing of some primers (6). Indeed, an analysis of the polymorphisms described and the primers used showed that some strains harbor a one-base exchange in the 5Ј terminus of primer "seg forward" as well as in the sei primers.…”
Section: Resultsmentioning
confidence: 99%
“…Although sei and seg are encoded on the same pathogenicity island, the enterotoxin gene cluster egc, frequently only sei or seg was detected using the primer pairs described previously (26,28). This effect may be caused by the polymorphisms that were found in egc and that impede the annealing of some primers (6). Indeed, an analysis of the polymorphisms described and the primers used showed that some strains harbor a one-base exchange in the 5Ј terminus of primer "seg forward" as well as in the sei primers.…”
Section: Resultsmentioning
confidence: 99%
“…After entering into the bloodstream, the toxin affects the immune system by binding to the proteins of the class-II major histocompatibility complex and the activation of specific T-cell types, leading to a massive release of several cytokines followed by systemic toxicity and suppression of the adaptive immune response, hence the typical clinical signs -multiple organ dysfunction syndrome and eventually fatal shock (Fueyo et al, 2005;Omoe et al, 2005;Vasconcelos et al, 2010). Circulation of these strains in the food chains and human populations, particularly in immunocompromised patients, will increase the risk of developing the disease (Adesiyun et al, 1992;Blaiotta et al, 2006). Therefore, it is important to reveal subtypes and virulence factors of the circulating staphylococcal strains to develop effective control strategies against the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding staphylococcal enterotoxins may be located on plasmids, bacteriophages, transposons, or pathogenicity islands (PIs) and are transferred by horizontal gene transfer. Staphylococci present in food, showing the potential to produce enterotoxins, are serious threat to public health (Blaiotta et al 2006). Enterotoxins SEA, SEB, SEC, SED, called classic, cause more than 90% of cases of staphylococcal food poisoning (SFP).…”
Section: Introductionmentioning
confidence: 99%